Use substitution.
y = 2 - x and y = 4x + 7 can become
2 - x = 4x + 7
Now solve for x
-5 = 5x
-1 = x
Now plug -1 for x in either equation.
y = 2 - x -> y = 2 - (-1) -> y = 3
y = 4x + 7 -> y = 4*-1 + 7 -> y = -4 + 7 -> y = 3
So C) is the correct answer.
Answer:
Sarah is correct
Step-by-step explanation:
Required
Which of the students is correct
Let a number be x,
Given what the teacher asked the students to do, the solution is:
![Number = x](https://tex.z-dn.net/?f=Number%20%3D%20x)
![Opposite = -x](https://tex.z-dn.net/?f=Opposite%20%3D%20-x)
![Absolute = |x|](https://tex.z-dn.net/?f=Absolute%20%3D%20%7Cx%7C)
Only Sarah got this correctly; others are incorrect.
The proof is as follows.
For Sarah
![Number = 1416](https://tex.z-dn.net/?f=Number%20%3D%201416)
![Opposite = -1416](https://tex.z-dn.net/?f=Opposite%20%3D%20-1416)
![Absolute =|1416| = 1416](https://tex.z-dn.net/?f=Absolute%20%3D%7C1416%7C%20%3D%201416)
So, the numbers will be: 1416, -1416 and 1416
<em>Other students are incorrect</em>
Answer:
169.95
Step-by-step explanation:
Use formula Pi×r²
I believe the answer is A
Answer:
it'll be 64:5
Hope this helps
Hope this helps ALL THE BEST!!